PENGARUH PEMBERITAAN TERORISME DI MEDIA MASSA TERHADAP PERSEPSI MASYARAKAT MAKASSAR - Raidah Yusuf; Hafid Susanto (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2021)
The theory to be proven in this research is the hypodermic needle theory where media coverage can influence public perception, in this case terrorism and radicalism. Therefore, a quantitative study was prepared which aims to determine the effect of reporting on terrorism in the mass media on the perception of the people of Makassar. Respondents in this study were taken from the Makassar community, amounting to 1,469,601 according to the Makassar Central Statistics Agency. The sample selected in this study was 384 people with an error rate of 5%. The research data was obtained through a survey of respondents by distributing questionnaires. Then the data processing and analysis was carried out by simple linear regression analysis using the SPSS program. The results of this study indicate that there is an effect of reporting on terrorism in the mass media on the perception of the people of Makassar which is considered significant as the regression results obtained by the correlation/relationship value (R) which is 0.435. From the output, the coefficient of determination (R square) is 0.190, and the adjusted R square value is 0.187, which implies that the influence of the independent variable (news) on the dependent variable (perception) is 18.7%.